Comparison of Hip Functional Value and Quality of Life Between Cemented and Uncemented Hip Arthroplasty Patients - Legiran; Fredy Ferdinand Carol; Wiria Aryanta (Sriwijaya Journal of Surgery, 2018)
Abstract Introduction. Hip arthroplasty is aimed to reduce pain and restore hip joint function. Until now, the most optimal method for fixation in Hip Arthroplasty is controversial. The purpose of this study was to analyze the comparison of hip functional value and quality of life between cemented and uncemented hip arthroplasty patients. Methods. This study used cross sectional design. Data were collected via medical record and SF-12 questionnaire and Oxford hip score in patients who have received hip arthroplasty at general hospital Dr. Moh. Hoesin Palembang. Results: There were 43 cases found, consisting of 28 cemented cases and 15 uncemented cases. The average age was 60.42 ± 19.44 years with an age range of 24-88 years. 20 subjects (46.4%) and 23 subjects (53.5%) women. The most preoperative diagnosis was trauma / fracture (69.8%), followed by osteoarthritis (16.3%), osteonecrosis (4.7%). Previous normality tests have been done with the Sapiro-Wilk test and homogeneity test. A comparison of hip functional values ​​between cemented and uncemented hip arthroplasty patients had a value of p = 0.76 (p <0.05) meaning there was no significant difference. Comparison of quality of life between cemented and uncemented hip arthroplasty patients has a value of p = 0.592 (p <0.05) which also means there is no significant difference. Conclusion: There was no difference in pelvic functional value and quality of life between cemented and uncemented hip arthroplasty patients.